Early-stage effect of HIBD on neuro-motor function and organic composition of neurovascular units in neonatal rats - Mo, Yanjun; Zeng, Ying; Huo, Luyao; Liu, Gang; Tao, Jingwei; Jiang, Yu; Zhao, Tuo; Zhou, Zhuoluo; Mu, Xiaohong (Frontiers in Neuroscience, 2023)
Objective This study aimed to investigate the effects of neonatal hypoxic–ischemic brain damage (HIBD) on early-stage neuro-motor function, cerebral blood flow, and the neurovascular unit. Methods Twenty-four Sprague–Dawley newborn rats aged 7 days were obtained and randomly assigned to either the sham or the model group using a random number table. The HIBD model was established using the Rice-Vannucci method. After the induction of HIBD, the body weight of the rats was measured and their neuro-motor function was assessed. Further, cerebral blood flow perfusion was evaluated using laser speckle flow imaging, and immunofluorescent staining techniques were employed for examining the activation of specific markers and their morphological changes in different cell populations, which included vascular endothelial cells, neurons, astrocytes, and microglia within the motor cortex. Results After HIBD, the model group exhibited impaired neuro-motor function and growth. Cerebral blood flow perfusion decreased in both the hemispheres on day 1 and in the ipsilateral brain on day 4. However, no significant difference was observed between the two groups on day 7. Moreover, the CD31 and NeuN showed a sharp decline on day 1, which was followed by a gradual increase in the expression levels. The activated microglia and astrocytes formed clusters in the injured cortex. Notably, the regions with positive staining for Arg-1, Iba-1, CD68, and GFAP consistently displayed higher values in the model group as compared to that in the sham group. The total number of branch endpoints and microglia branches was higher in the model group than in the sham group. Immunofluorescent co-localization analysis revealed no co-staining between Iba-1 and Arg-1; however, the Pearson’s R-value for the co-localization of Iba-1 and CD68 was higher in the model group, which indicated an increasing trend of co-staining in the model group. Conclusion Early-stage neuro-motor function, cerebral blood flow, microvasculature, and neurons in neonatal rats exhibited a trend of gradual recovery over time. The activation and upregulation of neuroglial cells continued persistently after HIBD. Furthermore, the impact of HIBD on early-stage neuro-motor function in newborn rats did not synchronize with the activation of neuroglial cells. The recovery of neuro-motor function, microvasculature, and neurons occurred earlier than that of neuroglial cells.